Soft‐tissue re‐growth following fibre retention osseous resective surgery or osseous resective surgery: a multilevel analysis. (24th March 2015) - Cairo, Francesco; Carnevale, Gianfranco; Buti, Jacopo; Nieri, Michele; Mervelt, Jana; Tonelli, Paolo; Pagavino, Gabriella; Tonetti, Maurizio
Abstract Background The aim of this study was to assess soft‐tissue re‐growth following Fibre Retention Osseous Resective Surgery (FibReORS) or Osseous Resective Surgery (ORS) over a 12‐month healing period. Material and Methods Thirty patients with chronic periodontitis showing persistent periodontal pockets at posterior natural teeth after cause‐related therapy were enroled. Periodontal pockets were associated with infrabony defect ≤3 mm; 15 patients were randomly assigned to FibReORS (test group) and 15 to ORS (control group). Measurements were performed by a blind and calibrated examiner. Soft‐tissue rebound after flap suture was monitored by changes in gingival recession at 1‐, 3‐, 6‐, and 12‐ month follow‐up. Multilevel analysis considering patient, site, and time levels was performed. Results Greater osseous resection during surgery and higher post surgical gingival recession was observed in the ORS group. The mean amount of soft‐tissue rebound following surgery was 2.5 mm for ORS‐treated sites and 2.2 mm for FibReORS‐treated sites. Approximately 90% of the coronal re‐growth was detectable after 6 months for both procedures. The interaction between ORS and time of observation showed a higher soft‐tissue rebound after 12 months (p = 0.0233) for ORS‐treated sites. Conclusions Both procedures showed a similar coronal soft‐tissue re‐growth with a significant higher recession reduction for ORS‐treated sites. Significant clinical stability of the gingival margin is obtained 6 months after surgery for both procedures.